Enhancement of mechanical properties and corrosion resistance of cast iron alloy using CO2 laser surface treatment / Sameer K. Fayyadh, Enas A. Khalid and Abbas S. Alwan - K. Fayyadh, Sameer; A. Khalid, Enas; S. Alwan, Abbas (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2022)
This work aimed to study the effect of laser surface treatment on the mechanical characteristics and corrosion behaviour of grey cast iron type A159. Many technical applications used conventional surface treatment, but laser surface hardening has recently been used to enhance the surface properties of many alloys. The mechanical characteristics, including microstructure, microhardness, and wear resistance of A159 grey cast iron, were studied, in addition to corrosion behaviour. The experimental laser parameters in this work were 0.9, 1.2, and 1.5 KW power with continuous wave carbon dioxide lasers with scanning speeds of 10 and 12 mm/s were used. The results found that phase-transitional alterations in microstructure were influenced by laser therapy. Also, the microhardness increased with increasing power, with the maximum reaching approximately 950 HV while the base metal has an average of approximately 260 HV. Also, we found the power laser increased corrosion resistance by lowering the corrosion rate (CR) from 21.10 for the untreated sample to 1.02 (m.p.y.), additionally, corrosion protection efficiency (CPE) increased to 95.27 percent.